Zinc oxide nanoparticles alleviate the arsenic toxicity and decrease the accumulation of arsenic in rice (Oryza sativa L.) - Shiwei Yan (BMC Plant Biology, 2021)
Abstract Background Rice is particularly effective, compared to other cereals, at accumulating arsenic (As), a nonthreshold, class 1 human carcinogen in shoot and grain. Nano-zinc oxide is gradually used in agricultural production due to its adsorption capacity and as a nutrient element. An experiment was performed to explore the effects of zinc oxide nanoparticles (nZnO) on arsenic (As) toxicity and bioaccumulation in rice. Rice seedlings were treated with different levels of nZnO (0, 10, 20, 50, 100 mg/L) and As (0, and 2 mg/L) for 7 days. Results The research showed that 2 mg/L of As treatment represented a stress condition, which was evidenced by phenotypic images, seedling dry weight, chlorophyll, and antioxidant enzyme activity of rice shoot. The addition of nZnO (10–100 mg/L) enhanced the growth and photosynthesis of rice seedlings. As concentrations in the shoots and roots were decreased by a maximum of 40.7 and 31.6% compared to the control, respectively. Arsenite [As (III)] was the main species in both roots (98.5–99.5%) and shoots (95.0–99.6%) when exposed to different treatments. Phytochelatins (PCs) content up-regulated in the roots induced more As (III)-PC to be complexed and reduced As (III) mobility for transport to shoots by nZnO addition. Conclusion The results confirmed that nZnO could improve rice growth and decrease As accumulation in shoots, and it performs best at a concentration of 100 mg/L.